Antibiotic resistance in healthcare‐related and nosocomial spontaneous bacterial peritonitis. (7th December 2016) - Lutz, Philipp; Nischalke, Hans Dieter; Krämer, Benjamin; Goeser, Felix; Kaczmarek, Dominik J.; Schlabe, Stefan; Parcina, Marijo; Nattermann, Jacob; Hoerauf, Achim; Strassburg, Christian P.; Spengler, Ulrich
Abstract: Background: Spontaneous bacterial peritonitis (SBP) can be life threatening in patients with liver cirrhosis. In contrast to community‐acquired SBP, no standard treatment has been established for healthcare‐related and nosocomial SBP. Materials and methods: We prospectively collected healthcare‐related and nosocomial SBP cases from March 2012 till February 2016 at the Department of Internal Medicine I of the University of Bonn and analysed the prevalence of antibiotic resistance among the isolated bacteria. SBP was diagnosed according to international guidelines. Ciprofloxacin, ceftriaxone and meropenem were used as reference substance for resistance to quinolones, third‐generation cephalosporins and carbapenems, respectively. Results: Ninety‐two SBP episodes in 86 patients were identified: 63 episodes (69%) were nosocomial. Escherichia coli, Klebsiella species, enterococci and streptococci were most frequently isolated. Frequencies of these microorganisms were comparable for healthcare‐related and nosocomial SBP (14% vs. 11%, 14% vs. 8%, 14% vs. 5% and 10% vs. 6%, respectively). In general, antibiotic resistance was higher in isolates from nosocomial than from healthcare‐related SBP (50% vs. 18% for quinolones, 30% vs. 11% for piperacillin–tazobactam; P > 0·05), but comparable concerning third‐generation cephalosporins (30% vs. 33%). All microorganisms were sensitive to carbapenems apart from nosocomial infections with Enterococcus faecium ( n = 3) and Candida albicans ( n = 1) due to intrinsic resistance or lack of microbiological efficacy, respectively. No multidrug‐resistant microorganisms were detected. Resistance to initial antibiotic treatment affected 30‐day survival negatively (18% vs. 68%; P = 0·002). Conclusion: Resistance to initial antibiotic treatment was associated with increased mortality. With resistance to cephalosporins being frequent, piperacillin–tazobactam or carbapenems might be preferred as treatment of SBP.